Exercise training in patients with a left ventricular assist device (Ex‐VAD): rationale and design of a multicentre, prospective, assessor‐blinded, randomized, controlled trial. (28th March 2019) - Bobenko, Anna; Schoenrath, Felix; Knierim, Jan H.; Friede, Tim; Verheyen, Nicolas; Mehra, Mandeep R.; Haykowsky, Mark; Herrmann‐Lingen, Christoph; Duvinage, André; Pieske‐Kraigher, Elisabeth; Halle, Martin; Falk, Volkmar; et al.
Abstract : Aims: Left ventricular assist device (LVAD) therapy is a promising option for patients with advanced heart failure (HF), refractory to guideline‐mandated medical treatment either as a bridge to heart transplantation or as lifelong therapy. Functional capacity improves after LVAD implantation but remains reduced in patients with long‐term LVAD therapy. Exercise training (ET) improves functional capacity and quality of life (QoL) in HF and may provide incremental benefits in patients supported with LVAD therapy. Methods: The primary objective of Ex‐VAD is to investigate whether a 12‐week supervised ET can improve peak oxygen uptake (peakVO2 ) measured by cardiopulmonary exercise testing (CPET) on an ergometer. The study is powered to demonstrate a group difference of 3 mL/min/kg in peakVO2 at week 12, with a power of 0.9 and a standard deviation of 5 mL/min/kg. After baseline assessments to determine whether ET is safe, 66 patients at six trial sites with advanced HF and LVAD therapy will be randomized 2:1 to supervised ET or to the control arm of usual care alone. Patients randomized to ET will perform supervised aerobic endurance and resistance ET (three times/week) for 12 weeks. At baseline and during follow‐up, anthropometry, CPET, echocardiography (at rest and exercise), and QoL evaluation will be performed. Blood samples will be collected to examine cardiac‐specific relevant biomarkers. Overall physical activity, training sessions, and adherence will be monitored and documented throughout the study using accelerometers and patient diaries. Conclusions: The Ex‐VAD trial will assess the effects of a supervised ET programme on peakVO2 and QoL in patients with LVAD. As LVAD therapy moves from crisis support to ambulatory functional enhancement, this trial will provide a rationale to improve functional capacity and, in perspective, cardiovascular outcomes in LVAD‐supported patients with advanced HF.